Incorporation of WO3 species into TiO2 nanotubes via wet impregnation and their water-splitting performance - Lai, Chin Wei; Sreekantan, Srimala (Electrochimica acta, 2013)
[Display omitted] ► Hybrid WO3–TiO2 nanotubes were prepared using anodization and wet impregnation techniques. ► A maximum photocurrent density of up to 2.1mA/cm2 (η≈5.1%) was achieved. ► Lattice doping of the W6+ ions within TiO2 formed WOTi bonds in this binary system. ► Optimum WO3 content acted as an electron acceptor. ► Electrons trapped by WO3 transported rapidly from nanotube walls to the Ti substrate. Self-organized and highly ordered titanium dioxide (TiO2) nanotubes synthesized through anodization and wet impregnation were applied to incorporate tungsten trioxide (WO3) species uniformly throughout the walls of nanotubes. In this study, ammonium paratungstate (APT) was used as a precursor. The effect of APT molarity on the formation of WO3–TiO2 nanotubes was investigated using field emission microscopy, energy dispersion X-ray spectroscopy, transmission electron microscopy, X-ray diffraction, photoluminescence, and X-ray photoelectron spectroscopy. The WO3–TiO2 nanotubes dipped in 0.3mM APT aqueous solution exhibited better photoelectrochemical water-splitting performance under visible illumination. A maximum photocurrent of 2.1mA/cm2 with a photoconversion efficiency of 5.1% was obtained, which is approximately twice higher than that of pure TiO2 nanotubes. The findings were mainly attributed to higher charge carrier separation, which minimized the recombination losses and enhanced the transportation of photo-induced electrons in this binary hybrid photoelectrode.